Challenges in Laboratory Diagnosis of Malaria in a Low-Resource Country at Tertiary Care in Eastern Nepal: A Comparative Study of Conventional vs. Molecular Methodologies - Pragyan Dahal; Basudha Khanal; Keshav Rai; Vivek Kattel; Satish Yadav; Narayan Raj Bhattarai (Journal of Tropical Medicine)
For ongoing malaria elimination programmes, available methods such as microscopy and rapid diagnostic tests (RDTs) cannot detect all malaria cases in acute febrile illness. These methods are entirely dependent on the course of infection, parasite load, and skilled technical resources. Our study objectives were to estimate the performance of light microscopy and a RDT as well as real-time PCR for the detection of the Plasmodium parasite. Altogether, 52 blood samples collected from patients with acute febrile illness were tested by microscopy, RDT, and real-time PCR. The results were compared in terms of sensitivity and specificity. Microscopy detected the malaria parasite in 5.8% of the blood samples whereas 13.5% were detected by the RDT and 27% by real-time PCR. Considering real-time PCR as the gold standard method, microscopy had a sensitivity of 21.4% and a specificity of 100%, and the RDT had a sensitivity of 28.6% and a specificity of 92.1%. Microscopy together with the RDT successfully detected malaria positive cases in blood samples of Ct value below 20, but both were unable to detect malaria cases between 26–40 Ct value ranges amplified by real-time PCR. Despite various diagnostic tools being available, microscopy still remains the method of choice for diagnosis, while the RDT is user-friendly when applied at the point of care. However, our preliminary results emphasize the need to implement the test with higher sensitivity and specificity in the context of a malaria elimination programme. Such programmes can be a crucial opportunity to understand the species prevalent in a low-endemic region. However, these results should be further verified with a large cohort study to document the submicroscopic infection.